Daya Dukung Sistem Kesehatan Terhadap Transformasi Ekonomi Daerah Kepulauan yang Inklusif dan Berkelanjutan - Baharuddin Baharuddin (Jurnal Archipelago, 2025)
The support of the health system is crucial for the sustainable economic transformation of island regions. The health system is also inseparable from education programs. The relationship between the health system and sustainable economic development (transformation) can be established through empirical studies, surveys, and literature approaches. In literature studies, bibliometric analysis can be used. The main objective of this study is to examine the relationship between the health system and economic transformation in island regions. The method used in this study is bibliometric analysis with keyword co-occurrence as the unit of analysis, supplemented with relevant literature studies. Based on 1433 documents, four main clusters were obtained, namely health policy-public health, universal coverage-primary health care, health system strengthening, and digital health care-governance. The results of this study show a strong relationship between the health system and the economy and sustainable development (sustainable development) of a region. The results of this study can be used as empirical evidence for the basis of formulating regulations in island regions.